Severe ovarian hyperstimulation syndrome in a case of nonmutated recurrent genuine empty follicle syndrome - Sumina Mannur; Talha Jabeen; Mohd Abdul Khader; Ramanachary Namoju; Lendale Sai Shakti Rao (Wolters Kluwer Medknow Publications, 2021)
Empty follicle syndrome (EFS) is a rare event in which no oocytes are retrieved from apparently normal growing follicles with normal steroidogenesis despite meticulous follicular aspiration in assisted reproductive technology (ART) cycles. EFS is mainly of two types, genuine EFS and false EFS. Here, we report a case of a 24-year-old woman presenting with primary infertility with normal ovarian reserve and regular menstrual cycles, husband having severe "oligo-astheno-teratozoospermia," and planned for ART treatment. We could not retrieve any oocytes in successive cycles despite optimum human chorionic gonadotropin (hCG) levels on the day of oocyte retrieval and using different management protocols mentioned until now in the literature. The whole genomic analysis was found to be normal (46, XX). Further, the patient had experienced severe ovarian hyperstimulation syndrome (OHSS) after the second cycle of ovarian stimulation despite no luteal hCG support. We were ineffectual to find the cause of recurrent EFS in this patient and therefore counseled the patient for donor oocytes. This case highlights the difficulty in treating genuine EFS patients and the need for monitoring serum estradiol levels during ovarian stimulation to prevent another serious complication of OHSS.